Dictionaries : the art and craft of lexicography - Landau, S.I. Sidney I. Landau (New York : Cambridge University, 2001)
This second edition of Sidney I. Landau's landmark work offers a comprehensive and completely up-to-date description of how dictionaries are researched and written, with particular attention to the ways in which computer technology has changed modern lexicography. Landau has an insider's practical knowledge of making dictionaries and every feature of the dictionary is examined and explained. Written in a readable style, free of jargon and unnecessary technical language, it will appeal to readers with no specialist knowledge of the field, as well as to professional lexicographers.
Includes bibliographical references and index.
Keywords: Lexicography; Encyclopedias and dictionaries -- History and criticism